MICRO/NANO-TECHNOLOGY BASED RENEWABLE ENERGY DEVICES AND POSSIBILITIES – A DETAIL AND EXPERIMENTAL ASPECTS (International Journal of Engineering Sciences & Management Research, 2016)
The covered work covers the state of the art- micro electronics in the area of renewable energy sector. From the literature survey done at various levels, a lot of research done in micro level for benefit nature has been mentioned. As the green chemistry and green environment to be boost with the miniature technology to be used, nano electronics field in terms of use of 1dimensional (quantum dot/nano particle) to 2dimensional (nano wire) to 3 dimensional(nano sphere) to 4dimensional materials (nano origami/bio mimic). A lot of potential at nano level will help in shaping the nature, human kind and environment using renewable energy. Since 1996 a lot of work has been carried on under the aegis of micro electronics, which face some problem in globalization and miniaturization. Under nano electronics domain, the challenges of cost to be well optimized.